Power electronic control in electrical systems - Acha, Enrique (Newnes, 2002)
Within this book the fundamental concepts associated with the topic of power electronic control are covered alongside the latest equipment and devices, new application areas and associated computer-assisted methods. *A practical guide to the control of reactive power systems *Ideal for postgraduate and professional courses *Covers the latest equipment and computer-aided analysis.
Keywords: Electric power systems -- Control.; Power electronics.; elektronické knihy; electronic books